Analisis Putusan Hakim Terhadap Pertanggungjawaban Pidana Dalam Pembunuhan Yang Dilakukan Oleh Anak ( Studi Kasus Putusan Nomor : 15/Pid.Sus-Anak/2021/PN Amb) - Martha Adolfina Ohoiner; Julianus Edwin Latupeirissa; Erwin Ubwarin (Faculty of Law Universitas Pattimura, 2023)
Currently, many criminal acts are committed by children, this is due to developments in the times which make children easily influenced so that they commit unacceptable actions. One of the facts can be seen in the murder case committed by Rahman Bahari Ramadhan Alias ​​Babang against the victim named Firman Alias ​​Tole which was tried at the Ambon District Court as per Decision Number: 15/Pid.Sus-Anak/2021/PN Amb. It has been regulated in the Criminal Code regarding the consequences of committing an act of murder, but in society, murder is something that occurs continuously and must be prosecuted. The research used is normative legal research. The problem approaches used are the statutory approach and the conceptual approach. The collection of legal materials used includes primary, secondary and tertiary legal materials. Collection procedures using Legal Literature Materials as well as Management and Analysis of Legal Materials are carried out using qualitative analysis techniques to answer problems. Based on this research, it can be concluded that a child who commits a criminal act can be held accountable as determined by the Criminal Code and other laws and regulations. So, based on the judge's legal considerations, the child was sentenced to imprisonment for 4 (four) years and 6 (six) months, the sentence received by the child was based on the failure of the diversion process.